Performance enhancement of oxygen evolution reaction through incorporating bimetallic electrocatalysts in two-dimensional metal–organic frameworks. Issue 12 (29th May 2020) - Yang, Chun; Cai, Wen-Jing; Yu, Bin-Bin; Qiu, Hong; Li, Meng-Li; Zhu, Lian-Wen; Yan, Zheng; Hou, Lei; Wang, Yao-Yu
Abstract : We designed and synthesized a series of bimetallic and monometallic 2D metal–organic framework electrocatalysts with excellent stability, discussing their different electrochemical catalysts for oxygen evolution reaction (OER). Abstract : Bimetallic electrocatalysis with its superior performance has a broad application prospect in oxygen evolution reaction (OER), but the fundamental reason for improving the performance is still cramped. Three comparable two-dimensional (2D) metal–organic frameworks (MOFs) were designed and synthesized to explore the underlying mechanism. Among the examined 2D MOFs, CoFe-MOF exhibited the best OER performance compared with Co-MOF and CoNi-MOF . The proposed model of bimetallic and monometallic electrocatalysts affecting their OER performance can help to explore precise structure–performance relationships for a rational catalyst design at the atomic/molecular levels and understand the related catalytic mechanisms as well.